What to Expect from Code Review Bots on GitHub? A Survey with OSS Maintainers - Wessel, Mairieli; Serebrenik, Alexander; Wiese, Igor; Steinmacher, Igor; Gerosa, Marco A. (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2020)
Software bots are used by Open Source Software (OSS) projects to streamline the code review process. Interfacing between developers and automated services, code review bots report continuous integration failures, code quality checks, and code coverage. However, the impact of such bots on maintenance tasks is still neglected. In this paper, we study how project maintainers experience code review bots. We surveyed 127 maintainers and asked about their expectations and perception of changes incurred by code review bots. Our findings reveal that the most frequent expectations include enhancing the feedback bots provide to developers, reducing the maintenance burden for developers, and enforcing code coverage. While maintainers report that bots satisfied their expectations, they also perceived unexpected effects, such as communication noise and newcomers' dropout. Based on these results, we provide a series of implications for bot developers, as well as insights for future research.